The perceived impact of technological advancement on a telecommunications company’s competitive advantage in Johannesburg, South Africa - Pillay, Ryan Keegan (The IIE, 2020)
In recent years technology has been the focal point of everything, technology is an integrated part of everyone’s lives as majority of the world’s population uses technology in their daily lives. It is something that has drastically made living easier, made various things more accessible and has all in all helped the way the world has transcended and evolved. This study looked at how the technological landscape has shaped the way businesses operate and more importantly it aimed at finding the link between technological advancement and competitive advantage in a technologically intensive company. In-dept interviews were conducted between 10 participants who worked for technologically intensive firms, the aim of these interviews were to evaluate how each person perceived technological advancement and competitive advantage as well as it helped in gaining an inside look as to how the firms who these individuals worked for used technology to gain a competitive advantage. A thematic analysis study was used to evaluate each response and it was found that technological advancement has quite a significant impact on a firms competitive advantage and by using technological advancement greatly helped the companies be more effective and efficient in their competitive advantage achievement.
Keywords: Technological advancement; Telecommunications company; Competitive advantage; Johannesburg